The Health and Economic Impacts of Structural Energy Performance Investments in Wales: An Evaluation of the Arbed Programme. (2017) - Johnson, Rhodri; Rodgers, Sarah; Watkins, Alan; Poortinga, Wouter; Grey, Charlotte; Jiang, Shiyu; Anderson, Pippa; Lyons, Ronan A
No abstract available